2011
DOI: 10.1097/aud.0b013e31820a77e2
|View full text |Cite
|
Sign up to set email alerts
|

Using the Auditory Steady State Response to Record Response Amplitude Curves. A Possible Fast Objective Method for Diagnosing Dead Regions

Abstract: Cochlear dead regions (DRs) can be diagnosed by recording psychophysical tuning curves (PTCs). PTC recording methods are time consuming and cannot be applied to infants. We propose, using the auditory steady-state response, to record response amplitude curves by development of the method that could be used to diagnose and define DRs in infants whilst they are asleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The subjects received financial compensation for their time. The normally hearing subjects were the same subjects as reported in Wilding et al (2011).…”
Section: Methodsmentioning
confidence: 99%
“…The subjects received financial compensation for their time. The normally hearing subjects were the same subjects as reported in Wilding et al (2011).…”
Section: Methodsmentioning
confidence: 99%
“…Poor repeatability of ASSR f max was found between the two mirrored half-tracks; the coefficient of repeatability was 3.36 kHz. Wilding et al (2011) found a coefficient of repeatability for ASSR Response Amplitude Curve tip frequency between repeated recordings to be 0.39 kHz. The high repeatability coefficient of ASSR f max in our study may be due to a number of reasons.…”
Section: Assr Repeatabilitymentioning
confidence: 97%
“…The modulation frequency of 87 Hz meant that the ASSR originated mainly from the level of the brainstem (Luke et al, 2017;Rance, 2008;Weisz & Lithari, 2017). The carrier frequency of 2 kHz was chosen to allow comparisons of the results with those for other studies (Markessis et al, 2009;Wilding et al, 2011).…”
Section: Stimulimentioning
confidence: 99%
See 2 more Smart Citations